Comparative evaluation of the modulatory role of 1,25-dihydroxy-vitamin D3 on endoplasmic reticulum stress-induced effects in 2D and 3D cultures of the intestinal porcine epithelial cell line IPEC-J2 - Wen, Gaiping; Eder, Klaus; Ringseis, Robert; Justus Liebig University Giessen (My University, 2024)
Background: The use of conventional two-dimensional (2D) culture of the porcine intestinal epithelial cell (IEC) line IPEC-J2 in animal nutrition research has the disadvantage that IEC function is studied under unphysiological conditions, which limits the ability of transferring knowledge to the in vivo-situation. Thus, the aim of the present study was to establish a more convincing and meaningful three-dimensional (3D) culture of IPEC-J2 cells, which allows to study cell function in a more tissue-like environment, and to compare the effect of the endoplasmic reticulum (ER) stress inducer tunicamycin (TM) on ER stress indicators and the expression of tight junction proteins (TJP), inflammatory and apoptosis-related genes and the modulatory role of 1,25-dihydroxy-vitamin D3 (1,25D3) on these parameters in 2D and 3D cultures of IPEC-J2 cells. Results: A published protocol for 3D culture of Caco-2 cells was successfully adopted to IPEC-J2 cells as evident from fully differentiated 3D IPEC-J2 spheroids showing the characteristic spherical architecture with a single layer of IPEC-J2 cells surrounding a central lumen. Treatment of 2D IPEC-J2 cells and 3D IPEC-J2 spheroids with TM for 24 h markedly increased mRNA and/or protein levels of the ER stress target genes, heat shock protein family A (Hsp70) member 5 (HSPA5) and DNA damage inducible transcript 3 (DDIT3), whereas co-treatment with TM and 1,25D3 did not mitigate TM-induced ER stress in IPEC-J2 cells in the 2D and the 3D cell culture. In contrast, TM-induced expression of pro-inflammatory [interleukin-6 (IL6), IL8] and pro-apoptotic genes [BCL2 associated X, apoptosis regulator (BAX), caspase 3 (CASP3), CASP8] and genes encoding TJP [TJP1, claudin 1 (CLDN1), CLDN3, occludin (OCLN), cadherin 1 (CDH1), junctional adhesion molecule 1 (JAM1)] was reduced by co-treatment with TM and 1,25D3 in 3D IPEC-J2 spheroids but not in the 2D cell culture. Conclusions: The effect of 1,25D3 in the IPEC-J2 cell culture is dependent on the culture model applied. While 1,25D3 does not inhibit TM-induced expression of genes involved in inflammation, apoptosis and TJP in conventional 2D cultures of IPEC-J2 cells, TM-induced expression of these genes is abrogated by 1,25D3 in the more meaningful 3D IPEC-J2 cell culture model.
Keywords: ddc:640; ddc:360